Business ethics concepts & cases - Velasquez, Manuel G. (Upper Saddle River, N.J. Pearson Prentice Hall, 2006)
CD-ROM contains: ABC news segments: Enron's fall -- Unocal in Burma -- AIDS in Africa -- Mircosoft antitrust trial -- To drill or not to drill -- Ford/Firestone debacle -- Ralphs -- Gap's labor problems.
Ethics and business -- Ethical principles in business -- The business system: government, markets and international trade -- Ethics in the marketplace -- Ethics and the environment -- The ethics of consumer production and marketing -- The ethics of job discrimination -- The individual in the organization.
Includes bibliographical references (pages 407-431) and index.
Keywords: Business ethics; Business ethics -- Case studies; Business ethics; Business ethics -- Case studies